Business Plan: Trading in Pre-Owned Building Materials In Saudi Arabia - Krimly, Salah (2015)
The business plan is to establish a new investment in the Saudi building and construction market. The investment will be in trading the pre-owned building materials. The materials selected are not construction materials but they are finishing materials. However, the Saudi building and construction market is growing and the Saudi government are supporting the construction and the real estate market. Also, a recent researches shows the acceptance of the Saudi citizen to use the pro-owned materials if it is in a good quality and reasonable prices. The business plan will be divided into seven sections. The first section will be and executive summary of the investment. The second section will illustrate the current situation and our vision, mission and values. The third section will discuss the external environment which includes a PEST analysis, market and competitor analysis and the competitor advantages. The following section will demonstrate the new business strategies and the operation strategies. The fifth section will cover all the financial analysis such as the investment costs, profit and loss accounts, breakeven analysis, the balance sheet and the cash flow. Than following section will include the risk analysis and finally is the concluding.